The structure of fractional spaces generated by a two-dimensional elliptic differential operator and its applications

  • Allaberen Ashyralyev1, 2,

    Affiliated with

    • Sema Akturk1 and

      Affiliated with

      • Yasar Sozen1, 3Email author

        Affiliated with

        Boundary Value Problems20142014:3

        DOI: 10.1186/1687-2770-2014-3

        Received: 30 October 2013

        Accepted: 3 December 2013

        Published: 2 January 2014

        Abstract

        We consider the two-dimensional differential operator A u ( x 1 , x 2 ) = a 11 ( x 1 , x 2 ) u x 1 x 1 ( x 1 , x 2 ) a 22 ( x 1 , x 2 ) u x 2 x 2 ( x 1 , x 2 ) + σ u ( x 1 , x 2 ) defined on functions on the half-plane Ω = R + × R with the boundary conditions u ( 0 , x 2 ) = 0 , x 2 R , where a i i ( x 1 , x 2 ) , i = 1 , 2 , are continuously differentiable and satisfy the uniform ellipticity condition a 11 2 ( x 1 , x 2 ) + a 22 2 ( x 1 , x 2 ) δ > 0 , σ > 0 . The structure of the fractional spaces E α ( A , C β ( Ω ) ) generated by the operator A is investigated. The positivity of A in Hölder spaces is established. In applications, theorems on well-posedness in a Hölder space of elliptic problems are obtained.

        MSC: 35J25, 47E05, 34B27.

        Keywords

        positive operator fractional spaces Green’s function Hölder spaces

        1 Introduction

        It is well known that (see, for example, [13] and the references therein) various classical and non-classical boundary value problems for partial differential equations can be considered as an abstract boundary value problem for an ordinary differential equation in a Banach space with a densely defined unbounded operator. The importance of the positivity property of the differential operators in a Banach space in the study of various properties for partial differential equations is well known (see, for example, [47] and the references therein). Several authors have investigated the positivity of a wider class of differential and difference operators in Banach spaces (see [818] and the references therein).

        Let us give the definition of positive operators and introduce the fractional spaces and preliminary facts that will be needed in the sequel.

        The operator A is said to be positive in E if its spectrum σ ( A ) lies inside of the sector S of the angle ϕ, 0 < 2 ϕ < 2 π , symmetric with respect to the real axis, and the following estimate (see, for example, [6, 19])
        ( A λ ) 1 E E M ( ϕ ) 1 + | λ |

        holds on the edges S 1 ( ϕ ) = { ρ e i ϕ : 0 ρ < } , S 2 ( ϕ ) = { ρ e i ϕ : 0 ρ < } of S, and outside of the sector S. The infimum of all such angles ϕ is called the spectral angle of the positive operator A and is denoted by ϕ ( A , E ) . We say that A is a strongly positive operator in E if ϕ ( A , E ) < π / 2 .

        Throughout the article, M indicates positive constants which may differ from time to time, and we are not interested to precise. If the constant depends only on α , β ,  , then we will write M ( α , β , ) .

        With the help of the positive operator A, we introduce the fractional space E β = E β ( E , A ) ( 0 < β < 1 ), consisting of all elements v E for which the norm
        v E β = sup λ > 0 λ β A ( λ + A ) 1 v E + v E

        is finite.

        Theorem 1 [20]

        Let 1 p + 1 q = 1 , p > 1 , and let f , g : R + R be any two nonnegative integrable functions such that 0 < 0 f p ( x ) d x < and 0 < 0 g q ( y ) d y < . Then the following Hilbert’s inequality holds:
        0 0 f ( x ) g ( y ) x + y d x d y < π csc ( π p ) ( 0 f p ( x ) d x ) 1 p ( 0 g q ( y ) d y ) 1 q .

        Danelich in [12] considered the positivity of a difference analog A h x of the 2m th-order multi-dimensional elliptic operator A x with dependent coefficients on semi-spaces R + × R n 1 .

        The structure of fractional spaces generated by positive multi-dimensional differential and difference operators on the space R n in Banach spaces has been well investigated (see [2123] and the references therein).

        In papers [19, 2427] the structure of fractional spaces generated by positive one-dimensional differential and difference operators in Banach spaces was studied. Note that the structure of fractional spaces generated by positive multi-dimensional differential and difference operators with local and nonlocal conditions on Ω R n in Banach spaces C ( Ω ) has not been well studied.

        In the present paper, we study the structure of fractional spaces generated by the two-dimensional differential operator
        A u ( x 1 , x 2 ) = a 11 ( x 1 , x 2 ) u x 1 x 1 ( x 1 , x 2 ) a 22 ( x 1 , x 2 ) u x 2 x 2 ( x 1 , x 2 ) + σ u ( x 1 , x 2 ) ,
        (1)
        defined over the region R + 2 = R + × R with the boundary condition u ( 0 , x 2 ) = 0 , x 2 R . Here, the coefficients a i i ( x 1 , x 2 ) , i = 1 , 2 , are continuously differentiable and satisfy the uniform ellipticity
        a 11 2 ( x 1 , x 2 ) + a 22 2 ( x 1 , x 2 ) δ > 0 ,

        and σ > 0 .

        Following the paper [12], passing limit when h 0 in the special case m = 1 and n = 2 , we get that there exists the inverse operator ( A + λ ) 1 for all λ 0 and the following formula
        ( A + λ ) 1 f ( x 1 , x 2 ) = 0 G ( x 1 , x 2 , p , s , λ ) f ( p , s ) d s d p
        (2)
        holds, where G ( x 1 , x 2 , p , s , λ ) is the Green function of differential operator (1). Moreover, the following estimates
        | G ( x 1 , x 2 , p , s , λ ) | C exp { a ( λ + 1 ) 1 / 2 ( | x 1 p | + | x 2 s | ) } × ( 1 + ln { 1 + ( ( λ + 1 ) 1 / 2 ( | x 1 p | + | x 2 s | ) ) 1 } ) ,
        (3)
        and
        | G x 1 ( x 1 , x 2 , p , s , λ ) | , | G x 2 ( x 1 , x 2 , p , s , λ ) | C exp { a ( λ + 1 ) 1 / 2 ( | x 1 p | + | x 2 s | ) } ( | x 1 p | + | x 2 s | ) 1
        (4)

        hold. Here a = a ( σ ) .

        Next, to formulate our result, we need to introduce the Hölder space C β = C β ( R + 2 ) of all continuous bounded functions φ defined on R + 2 satisfying a Hölder condition with the indicator β [ 0 , 1 ] with the norm
        f C β ( R + 2 ) = f C ( R + 2 ) + sup ( x 1 , x 2 ) , ( x 1 , x 2 ) R + 2 ( x 1 , x 2 ) ( x 1 , x 2 ) | f ( x 1 , x 2 ) f ( x 1 , x 2 ) | ( | x 1 x 1 | 2 + | x 2 x 2 | 2 ) β .
        Here, C ( R + 2 ) denotes the Banach space of all continuous bounded functions φ defined on R + 2 with the norm
        φ C ( R + 2 ) = sup ( x 1 , x 2 ) R + 2 | φ ( x 1 , x 2 ) | .

        Clearly, from estimates (3) and (4) it follows that A is a positive operator in C ( R + 2 ) . Namely, we have the following.

        Theorem 2 Let λ 0 . Then the following estimate
        ( A + λ ) 1 C ( R + 2 ) C ( R + 2 ) M 1 + λ

        is valid.

        Here, the structure of fractional spaces generated by the operator A is investigated. The positivity of A in Hölder spaces is studied. The organization of the present paper is as follows. In Section 2, the positivity of A in Hölder spaces is established. In Section 3, the main theorem on the structure of fractional spaces E α ( A , C β ( R + 2 ) ) generated by A is investigated. In Section 4, applications on theorems on well-posedness in a Hölder space of parabolic and elliptic problems are presented. Finally, the conclusion is given.

        2 Positivity of A in Hölder spaces C β ( R + 2 )

        Theorem 3 Let β ( 0 , 1 ) . For λ 0 , we have the following estimate:
        ( A + λ ) 1 C β ( R + 2 ) C β ( R + 2 ) M ( a ) 1 + λ .
        Proof Applying formula (2), the triangle inequality, the definition of C β -norm, estimate (3), and Hilbert’s inequality, we get
        | ( A + λ ) 1 f ( x 1 , x 2 ) | 0 | G ( x 1 , x 2 , p , s , λ ) | | f ( p , s ) | d s d p M f C β 0 e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) × ( 1 + ln { 1 + ( ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) ) 1 } ) d s d p M f C β [ 0 e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) d s d p + 0 e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) ( ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) ) 1 d s d p ] M 1 ( a ) 1 + λ f C β + M 2 ( a ) ( 1 + λ ) 1 / 2 f C β 0 0 e a ( 1 + λ ) 1 / 2 ( p + s ) p + s d s d p M 3 ( a ) 1 + λ f C β for  ( x 1 , x 2 ) R + 2 .
        Then from that it follows
        sup ( x 1 , x 2 ) R + 2 | ( A + λ ) 1 f ( x 1 , x 2 ) | M 3 ( a ) 1 + λ f C β .
        (5)
        Without loss of generality, we can put τ , h > 0 . Using formula (2) and the triangle inequality, we get
        | ( A + λ ) 1 [ f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) β / 2 ] | 1 ( τ 2 + h 2 ) β / 2 0 | G ( x 1 + τ , x 2 + h , p , s ; λ ) G ( x 1 , x 2 , p , s , λ ) | × | f ( p , s ) | d s d p
        (6)
        for ( x 1 , x 2 ) , ( x 1 + τ , x 2 + h ) R + 2 . Now, we will estimate the right-hand side of inequality (6). Let us consider two cases τ 2 + h 2 < 1 and τ 2 + h 2 1 separately. First, we consider the case τ 2 + h 2 < 1 . Using the triangle inequality, estimate (4), the definition of C β -norm, Hilbert’s inequality, and the Lagrange theorem, it follows that for some x 1 between x 1 , x 1 + τ , and x 2 between x 2 , x 2 + h ,
        | ( A + λ ) 1 [ f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) β / 2 ] | M 4 f C β [ τ ( τ 2 + h 2 ) β / 2 0 | G x 1 ( x 1 , x 2 , p , s ; λ ) | d s d p + h ( τ 2 + h 2 ) β / 2 0 | G x 2 ( x 1 , x 2 , p , s ; λ ) | d s d p ] M 4 f C β [ 0 | G x 1 ( x 1 , x 2 , p , s ; λ ) | d s d p + 0 | G x 2 ( x 1 , x 2 , p , s ; λ ) | d s d p ] M 5 f C β 0 e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) | x 1 p | + | x 2 s | d s d p M 6 ( a ) 1 + λ f C β .
        (7)
        Second, we consider the case τ 2 + h 2 1 . Using formula (2), the triangle inequality, estimate (3), the definition of C β -norm, and estimate (6), we get
        | ( A + λ ) 1 [ f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) β / 2 ] | M 7 f C β [ 0 e a ( 1 + λ ) 1 / 2 ( | x 1 + τ p | + | x 2 + h s | ) × ( 1 + ln { 1 + ( ( λ + 1 ) 1 / 2 ( | x 1 + τ p | + | x 2 + h s | ) ) 1 } ) d s d p + 0 e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) × ( 1 + ln { 1 + ( ( λ + 1 ) 1 / 2 ( | x 1 p | + | x 2 s | ) ) 1 } ) d s d p ] M 8 ( a ) 1 + λ f C β .
        (8)
        Estimates (7) and (8) yield that
        sup ( x 1 + τ , x 2 + h ) , ( x 1 , x 2 ) R + 2 ( τ , h ) ( 0 , 0 ) | ( A + λ ) 1 [ f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) β / 2 ] | M 8 ( a ) 1 + λ f C β .
        (9)
        Combining estimates (5) and (9), we obtain
        ( A + λ ) 1 C β ( R + 2 ) C β ( R + 2 ) M ( a ) 1 + λ .

        This finishes the proof of Theorem 3. □

        Note that from the commutativity of A and its resolvent ( A + λ ) 1 , and Theorem 3, we have the following theorem.

        Theorem 4 Let λ 0 . Then the following estimate holds:
        ( A + λ ) 1 E α ( A , C β ( R + 2 ) ) E α ( A , C β ( R + 2 ) ) M ( a ) 1 + λ .

        3 The structure of fractional spaces E α ( A , C β ( R + 2 ) )

        Suppose β, 2 α + β ( 0 , 1 ) . Consider the fractional space E α ( A , C β ( R + 2 ) ) and the Hölder space C 2 α + β ( R + 2 ) . In this section, we prove the following structure theorem.

        Theorem 5 The norms of the spaces E α ( A , C β ( R + 2 ) ) and C 2 α + β ( R + 2 ) are equivalent.

        Proof Assume that f C 2 α + β ( R + 2 ) . Let ( x 1 , x 2 ) R + 2 and λ > 0 be fixed. From formula (2) it follows that
        A ( A + λ ) 1 f ( x 1 , x 2 ) = 1 λ + 1 f ( x 1 , x 2 ) + λ 0 G ( x 1 , x 2 , p , s , λ ) ( f ( x 1 , x 2 ) f ( p , s ) ) d s d p .
        (10)
        Using equation (10), the triangle inequality, the following inequalities
        ( a + b ) p 2 p ( a p + b p ) , 0 < p < 1 , a , b 0 ,
        (11)
        ( a t ) θ e a t M , a > 0 , θ [ 0 , 1 ] ,
        (12)
        estimates (10), (11), (12), and the definition of C 2 α + β -norm, we obtain
        | λ α A ( A + λ ) 1 f ( x 1 , x 2 ) | λ α λ + 1 | f ( x 1 , x 2 ) | + λ α + 1 0 | G ( x 1 , x 2 , p , s , λ ) | | f ( x 1 , x 2 ) f ( p , s ) | d s d p M 9 f C 2 α + β [ λ α λ + 1 + λ α + 1 0 | G ( x 1 , x 2 , p , s , λ ) | × ( | x 1 p | 2 + | x 2 s | 2 ) α + β / 2 d s d p ] M 10 f C 2 α + β [ λ α λ + 1 + λ α + 1 0 e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) × ( 1 + ln { 1 + ( ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) ) 1 } ) ( | x 1 p | 2 + | x 2 s | 2 ) α + β / 2 d s d p ] M 11 ( a ) f C 2 α + β [ λ α λ + 1 + λ α + 1 ( 1 + λ ) 1 + α + β / 2 ] M 12 ( a ) f C 2 α + β for  ( x 1 , x 2 ) R + 2 .
        (13)
        Thus, it follows from estimate (13) that
        sup λ > 0 sup ( x 1 , x 2 ) R + 2 | λ α A ( A + λ ) 1 f ( x 1 , x 2 ) | M 12 ( a ) f C 2 α + β .
        (14)
        Let λ > 0 and ( x 1 , x 2 ) R + 2 be fixed. Using equation (10), we can write
        λ α A ( A + λ ) 1 [ f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) β / 2 ] = λ α λ + 1 [ f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) β / 2 ] + λ α + 1 0 G ( x 1 + τ , x 2 + h , p , s ; λ ) [ f ( x 1 + τ , x 2 + h ) f ( p , s ) ( τ 2 + h 2 ) β / 2 ] d s d p λ α + 1 0 G ( x 1 , x 2 , p , s ; λ ) [ f ( x 1 , x 2 ) f ( p , s ) ( τ 2 + h 2 ) β / 2 ] d s d p .
        (15)
        Now, we will estimate the right-hand side of equation (15). We consider two cases τ 2 + h 2 < 1 and τ 2 + h 2 1 , respectively. Let us first assume that τ 2 + h 2 < 1 . Furthermore, this situation will be considered in two cases: ( 1 + λ ) ( τ 2 + h 2 ) 1 and ( 1 + λ ) ( τ 2 + h 2 ) 1 . Let ( 1 + λ ) ( τ 2 + h 2 ) 1 . From equation (15), the triangle inequality, the definition of C 2 α + β -norm, the assumptions τ 2 + h 2 < 1 and ( 1 + λ ) ( τ 2 + h 2 ) 1 , it follows that
        | λ α A ( A + λ ) 1 [ f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) β / 2 ] | M 13 f C 2 α + β [ λ α ( 1 + λ ) ( τ 2 + h 2 ) β / 2 + λ α + 1 ( τ 2 + h 2 ) β / 2 0 | G ( x 1 + τ , x 2 + h , p , s ; λ ) | × ( | x 1 + τ p | 2 + | x 2 + h s | 2 ) α + β / 2 d s d p + λ α + 1 ( τ 2 + h 2 ) β / 2 0 | G ( x 1 , x 2 , p , s ; λ ) | ( | x 1 p | 2 + | x 2 s | 2 ) α + β / 2 d s d p ] = M 13 f C 2 α + β [ J 1 + J 2 + J 3 ] .
        (16)

        We will estimate J i , i = 1 , 2 , 3 , separately.

        First, let us estimate J 1 . Clearly, by the assumption ( 1 + λ ) ( τ 2 + h 2 ) 1 , we have
        J 1 1 .
        (17)
        From estimates (3), (11), (12), and the assumption ( 1 + λ ) ( τ 2 + h 2 ) 1 , it follows that
        J 2 M 14 λ α + 1 ( τ 2 + h 2 ) β / 2 0 e a ( 1 + λ ) 1 / 2 ( | x 1 + τ p | + | x 2 + h s | ) × ( 1 + ln { 1 + ( ( λ + 1 ) 1 / 2 ( | x 1 + τ p | + | x 2 + h s | ) ) 1 } ) × ( | x 1 + τ p | 2 + | x 2 + h s | 2 ) α + β / 2 d s d p M 15 ( a ) λ α + 1 ( 1 + λ ) 1 + α + β / 2 ( τ 2 + h 2 ) β / 2 M 15 ( a ) .
        (18)
        Estimates (3), (11), (12), and the assumption ( 1 + λ ) ( τ 2 + h 2 ) 1 yield that
        J 3 M 16 λ α + 1 ( τ 2 + h 2 ) β / 2 0 e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) × ( 1 + ln { 1 + ( ( λ + 1 ) 1 / 2 ( | x 1 p | + | x 2 s | ) ) 1 } ) ( | x 1 p | 2 + | x 2 s | 2 ) α + β / 2 d s d p M 17 ( a ) λ α + 1 ( 1 + λ ) 1 + α + β / 2 ( τ 2 + h 2 ) β / 2 M 17 ( a ) .
        (19)
        Combining estimates (17)-(19), we get
        | λ α A ( A + λ ) 1 [ f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) β / 2 ] | M 18 ( a ) f C 2 α + β .
        (20)
        Now, let us consider the case ( 1 + λ ) ( τ 2 + h 2 ) 1 . Then, using equation (10), we can write
        λ α A ( A + λ ) 1 [ f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) β / 2 ] = λ α λ + 1 [ f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) β / 2 ] + λ α + 1 0 G ( x 1 + τ , x 2 + h , p , s ; λ ) [ f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) β / 2 ] d s d p + λ α + 1 0 [ G ( x 1 + τ , x 2 + h , p , s ; λ ) G ( x 1 , x 2 , p , s ; λ ) ] × [ f ( x 1 , x 2 ) f ( p , s ) ( τ 2 + h 2 ) β / 2 ] d s d p .
        (21)
        From equation (21), the triangle inequality, the Lagrange theorem, the definition of C 2 α + β -norm, and the assumption τ 2 + h 2 < 1 , it follows that for some x 1 between x 1 , x 2 + τ , and x 2 between x 2 , x 2 + h ,
        | λ α A ( A + λ ) 1 [ f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) β / 2 ] | M 19 f C 2 α + β [ λ α λ + 1 ( τ 2 + h 2 ) α + λ α + 1 ( τ 2 + h 2 ) α × 0 | G ( x 1 + τ , x 2 + h , p , s ; λ ) | d s d p + λ α + 1 τ ( τ 2 + h 2 ) β / 2 0 | G x 1 ( x 1 , x 2 , p , s ; λ ) | ( | x 1 p | 2 + | x 2 s | 2 ) α + β / 2 d s d p + λ α + 1 h ( τ 2 + h 2 ) β / 2 0 | G x 2 ( x 1 , x 2 , p , s ; λ ) | ( | x 1 p | 2 + | x 2 s | 2 ) α + β / 2 d s d p ] = M 19 f C 2 α + β [ L 1 + L 2 + L 3 + L 4 ] .
        We will estimate L i , i = 1 , , 4 , separately. Let us start with L 1 . Clearly, we have
        L 1 1 .
        (22)
        Using estimates (3), (4), (11), (12), we obtain
        L 2 M 20 λ 0 e a ( 1 + λ ) 1 / 2 ( | x 1 + τ p | + | x 2 + h s | ) × ( 1 + ln { 1 + ( ( λ + 1 ) 1 / 2 ( | x 1 + τ p | + | x 2 + h s | ) ) 1 } ) d s d p M .
        (23)
        Note that by the triangle inequality and the fact that x 1 between x 1 , x 1 + τ , we get
        | x 1 p | | x 1 p | | x 1 x 1 | | x 1 p | τ ,
        (24)
        | x 2 s | | x 2 s | | x 2 x 2 | | x 2 s | h .
        (25)
        By inequalities (11), (12), estimates (4), (24), (25), and Hilbert’s inequality, we have
        L 3 M 21 λ α + 1 τ ( τ 2 + h 2 ) β / 2 0 e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) | x 1 p | + | x 2 s | ( | x 1 p | + | x 2 s | ) 2 α + β d s d p M 22 λ α + 1 τ ( τ 2 + h 2 ) β / 2 0 e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) ( | x 1 p | + | x 2 s | ) 2 α + β 1 d s d p + M 22 λ α + 1 τ ( τ 2 + h 2 ) β / 2 0 e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) × ( | x 1 p | + | x 2 s | ) 1 ( τ + h ) 2 α + β d s d p M 23 ( a ) [ λ α + 1 τ ( 1 + λ ) 1 + α + β / 2 ( τ 2 + h 2 ) β / 2 + λ α + 1 τ ( τ + h ) 2 α + β ( 1 + λ ) ( τ 2 + h 2 ) β / 2 ] M 24 ( a ) .
        (26)
        Similarly, we get
        L 4 M 24 ( a ) .
        (27)
        Combining estimates (22), (23), (26), (27), we obtain that for τ 2 + h 2 < 1 , ( 1 + λ ) 1 / 2 ( τ 2 + h 2 ) 1 ,
        | λ α A ( A + λ ) 1 [ f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) β / 2 ] | M 25 ( a ) f C 2 α + β .
        (28)
        It follows from estimates (20) and (28) that for τ 2 + h 2 < 1 , λ > 0 ,
        | λ α A ( A + λ ) 1 [ f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) β / 2 ] | M 26 ( a ) f C 2 α + β .
        (29)
        Next, let us assume that τ 2 + h 2 1 . By equation (10), we have
        λ α A ( A + λ ) 1 [ f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) β / 2 ] = λ α λ + 1 [ f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) β / 2 ] + λ α + 1 0 G ( x 1 + τ , x 2 + h , p , s ; λ ) [ f ( x 1 + τ , x 2 + h ) f ( p , s ) ( τ 2 + h 2 ) β / 2 ] d s d p λ α + 1 0 G ( x 1 , x 2 , p , s ; λ ) [ f ( x 1 , x 2 ) f ( p , s ) ( τ 2 + h 2 ) β / 2 ] d s d p .
        (30)
        Equation (30), estimates (3), (11), Hilbert’s inequality, the triangle inequality, the definition of C 2 α + β -norm, and the assumption τ 2 + h 2 1 yield that for λ > 0 ,
        | λ α A ( A + λ ) 1 [ f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) β / 2 ] | M 27 f C 2 α + β [ 1 + λ α + 1 0 | G ( x 1 + τ , x 2 + h , p , s ; λ ) | × ( | x 1 + τ p | 2 + | x 2 + h s | 2 ) α + β / 2 d s d p + λ α + 1 0 | G ( x 1 , x 2 , p , s ; λ ) | ( | x 1 p | 2 + | x 2 s | 2 ) α + β / 2 d s d p M 28 ( a ) f C 2 α + β [ 1 + λ α + 1 ( 1 + λ ) 1 + α + β / 2 + λ α + 1 ( 1 + λ ) 1 + α + β / 2 ] M 29 ( a ) f C 2 α + β .
        (31)
        From estimates (29) and (31) it follows that
        sup λ > 0 sup ( x 1 + τ , x 2 + h ) , ( x 1 , x 2 ) R + 2 ( τ , h ) ( 0 , 0 ) | λ α A ( A + λ ) 1 [ f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) β / 2 ] | M 30 ( a ) f C 2 α + β .
        (32)
        Combining estimates (14) and (32), we obtain
        C 2 α + β ( R + 2 ) E α ( A , C β ( R + 2 ) ) .
        Now, we will prove that E α = E α ( A , C β ( R + 2 ) ) C 2 α + β ( R + 2 ) . By Theorem 4, A is a positive operator in the Banach space E α . Hence, for V E α , we have
        V = 0 A ( λ + A ) 2 V d λ .
        (33)
        Let f E α . It follows from formula (2) and equation (33) that
        f ( x 1 , x 2 ) = 0 A ( λ + A ) 2 f ( x 1 , x 2 ) d λ = 0 0 G ( x 1 , x 2 , p , s ; λ ) A ( λ + A ) 1 f ( p , s ) d s d p d λ .
        (34)
        Using the triangle inequality, equation (34), estimate (3), and the definition of E α -norm, we obtain
        | f ( x 1 , x 2 ) | M 31 f E α 0 0 1 λ α e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) × ( 1 + ln { 1 + ( ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) ) 1 } ) d s d p d λ M 32 ( a ) f E α 0 1 λ α ( 1 + λ ) d λ M 33 ( a ) α ( 1 α ) f E α .
        Thus,
        sup ( x 1 , x 2 ) R + 2 | f ( x 1 , x 2 ) | M 33 ( a ) α ( 1 α ) f E α .
        (35)
        Let ( x 1 , x 2 ) R + 2 be fixed. From equation (34) it follows that
        f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) α + β / 2 = 0 0 G ( x 1 + τ , x 2 + h , p , s ; λ ) ( τ 2 + h 2 ) α + β / 2 λ α λ α A ( A + λ ) 1 × ( f ( p , s ) f ( x 1 , x 2 ) ) d s d p d λ 0 0 G ( x 1 , x 2 , p , s ; λ ) ( τ 2 + h 2 ) α + β / 2 λ α λ α A ( A + λ ) 1 ( f ( p , s ) f ( x 1 , x 2 ) ) d s d p d λ .
        (36)
        Now, we will estimate the right-hand side of equation (36). We consider two cases τ 2 + h 2 < 1 and τ 2 + h 2 1 . Let us first assume that τ 2 + h 2 < 1 . By equation (36), the triangle inequality, the Lagrange theorem, the definition of E α -norm, and the assumption τ 2 + h 2 < 1 , we have, for some x 1 between x 1 , x 1 + τ , and x 2 between x 2 , x 2 + h , that
        | f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) α + β / 2 | M 34 f E α [ 0 1 0 [ | G ( x 1 + τ , x 2 + h , p , s ; λ ) G ( x 1 , x 2 , p , s ; λ ) | ( τ 2 + h 2 ) α + β / 2 λ α ] × ( | x 1 p | 2 + | x 2 s | 2 ) β / 2 d s d p d λ + 1 1 / ( τ 2 + h 2 ) 0 [ | G ( x 1 + τ , x 2 + h , p , s ; λ ) G ( x 1 , x 2 , p , s ; λ ) | ( τ 2 + h 2 ) α + β / 2 λ α ] × ( | x 1 p | 2 + | x 2 s | 2 ) β / 2 d s d p d λ + 1 / ( τ 2 + h 2 ) 0 [ | G ( x 1 + τ , x 2 + h , p , s ; λ ) G ( x 1 , x 2 , p , s ; λ ) | ( τ 2 + h 2 ) α + β / 2 λ α ] × ( | x 1 p | 2 + | x 2 s | 2 ) β / 2 d s d p d λ ] = M 34 f E α [ I 1 + I 2 + I 3 ] .
        We will estimate I i , i = 1 , 2 , 3 , separately. Using the triangle inequality, estimates (4), (11), (25), (24), (12), the Lagrange theorem, and the assumption τ 2 + h 2 < 1 , we obtain
        I 1 M 35 [ 0 1 0 [ τ | G x 1 ( x 1 , x 2 , p , s ; λ ) | + h | G x 2 ( x 1 , x 2 , p , s ; λ ) | ( τ 2 + h 2 ) α + β / 2 λ α ] × ( | x 1 p | 2 + | x 2 s | 2 ) β / 2 d s d p d λ ] 0 1 0 [ e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) ( | x 1 p | + | x 2 s | ) λ α ] ( | x 1 p | 2 + | x 2 s | 2 ) β / 2 d s d p d λ M 36 [ 0 1 0 e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) ( | x 1 p | + | x 2 s | ) β λ α ( | x 1 p | + | x 2 s | ) d s d p d λ + 0 1 0 e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) ( τ + h ) β λ α ( | x 1 p | + | x 2 s | ) d s d p d λ ] M 37 ( a ) [ 0 1 1 λ α + β / 2 + 1 / 2 d λ + 0 1 1 λ α + 1 / 2 d λ ] M 38 ( a ) .
        From the triangle inequality, estimates (4), (11), (12), (24), (25), the Lagrange theorem, and the assumption τ 2 + h 2 < 1 , it follows that
        I 2 M 39 [ 1 1 / ( τ 2 + h 2 ) 0 [ τ | G x 1 ( x 1 , x 2 , p , s ; λ ) | + h | G x 2 ( x 1 , x 2 , p , s ; λ ) | ( τ 2 + h 2 ) α + β / 2 λ α ] × ( | x 1 p | 2 + | x 2 s | 2 ) β / 2 d s d p d λ ] M 40 [ 1 1 / ( τ 2 + h 2 ) 0 ( τ + h ) e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) ( | x 1 p | + | x 2 s | ) β ( τ 2 + h 2 ) α + β / 2 λ α ( | x 1 p | + | x 2 s | ) d s d p d λ ] M 41 [ 1 1 / ( τ 2 + h 2 ) 0 ( τ + h ) e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) ( | x 1 p | + | x 2 s | ) β ( τ 2 + h 2 ) α + β / 2 λ α ( | x 1 p | + | x 2 s | ) d s d p d λ + 1 1 / ( τ 2 + h 2 ) 0 ( τ + h ) e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) ( τ + h ) β ( τ 2 + h 2 ) α + β / 2 λ α ( | x 1 p | + | x 2 s | ) d s d p d λ ] M 42 ( a ) [ 1 1 / ( τ 2 + h 2 ) ( τ 2 + h 2 ) 1 / 2 ( τ 2 + h 2 ) α + β / 2 λ α + β / 2 + 1 / 2 d λ + 1 1 / ( τ 2 + h 2 ) ( τ 2 + h 2 ) 1 / 2 + β / 2 ( τ 2 + h 2 ) α + β / 2 λ α + 1 / 2 d λ ] M 43 ( a ) .
        Using the triangle inequality, estimates (3), (24), (25), (12), (11), the assumption τ 2 + h 2 < 1 , and the following estimate
        | x 1 p | = | x 1 p + τ τ | | x 1 p + τ | + τ , | x 2 s | = | x 2 s + h h | | x 2 s + h | + h ,
        we obtain
        I 3 M 44 [ 1 / ( τ 2 + h 2 ) 0 e a ( 1 + λ ) 1 / 2 ( | x 1 + τ p | + | x 2 + h s | ) ( τ 2 + h 2 ) α + β / 2 λ α × ( 1 + ln { 1 + ( ( λ + 1 ) 1 / 2 ( | x 1 + τ p | + | x 2 + h s | ) ) 1 } ) × ( | x 1 p + τ | + | x 2 s + h | + τ + h ) β d s d p d λ + 1 / ( τ 2 + h 2 ) 0 ( e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) × ( 1 + ln { 1 + ( ( λ + 1 ) 1 / 2 ( | x 1 p | + | x 2 s | ) ) 1 } ) ) / ( ( τ 2 + h 2 ) α + β / 2 λ α ) × ( | x 1 p | 2 + | x 2 s | 2 ) β / 2 d s d p d λ ] M 45 ( a ) [ 1 / ( τ 2 + h 2 ) 1 ( τ 2 + h 2 ) α + β / 2 λ α + β / 2 + 1 d λ + 1 / ( τ 2 + h 2 ) τ + h ( τ 2 + h 2 ) α + β / 2 λ α + 1 d λ ] M 46 ( a ) .
        Thus, for τ 2 + h 2 < 1 , we have
        | f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) α + β / 2 | M 47 ( a ) f E α .
        (37)
        Next, let us assume that τ 2 + h 2 1 . Using formula (36), estimate (3), the triangle inequality, Hilbert’s inequality, and the assumption τ 2 + h 2 1 , we get
        | f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) α + β / 2 | 0 0 | G ( x 1 + τ , x 2 + h , p , s ; λ ) | λ α | λ α A ( A + λ ) 1 f ( p , s ) | d s d p d λ + 0 0 | G ( x 1 , x 2 , p , s ; λ ) | λ α | λ α A ( A + λ ) 1 f ( p , s ) | d s d p d λ M 48 f E α [ 0 0 1 λ α e a ( 1 + λ ) 1 / 2 ( | x 1 + τ p | + | x 2 + h s | ) × ( 1 + ln { 1 + ( ( 1 + λ ) 1 / 2 ( | x 1 + τ p | + | x 2 + h s | ) ) 1 } ) d s d p d λ + 0 0 1 λ α e a ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) × ( 1 + ln { 1 + ( ( 1 + λ ) 1 / 2 ( | x 1 p | + | x 2 s | ) ) 1 } ) d s d p d λ ] M 49 ( a ) f E α 0 1 λ α ( 1 + λ ) d λ M 50 ( a ) α ( 1 α ) f E α .
        Hence, for τ 2 + h 2 1 , we obtain
        | f ( x 1 + τ , x 2 + h ) f ( t , x ) ( τ 2 + h 2 ) α + β / 2 | M 50 ( a ) α ( 1 α ) f E α .
        (38)
        Combining estimates (37) and (38), we get
        sup λ > 0 sup ( x 1 + τ , x 2 + h ) , ( x 1 , x 2 ) R + 2 ( τ , h ) ( 0 , 0 ) | f ( x 1 + τ , x 2 + h ) f ( x 1 , x 2 ) ( τ 2 + h 2 ) α + β / 2 | M 51 ( a ) α ( 1 α ) f E α .
        (39)
        Estimates (35) and (39) yield that
        E α = E α ( A , C β ( R + 2 ) ) C 2 α + β ( R + 2 ) .

        This is the end of the proof of Theorem 5. □

        4 Applications

        In this section, we consider some applications of Theorem 5. First, we consider the boundary value problem for the elliptic equation
        { 2 u ( y , x 1 , x 2 ) y 2 a 11 ( x 1 , x 2 ) 2 u ( y , x 1 , x 2 ) x 1 2 a 22 ( x 1 , x 2 ) 2 u ( y , x 1 , x 2 ) x 2 2 + σ u ( y , x 1 , x 2 ) = f ( y , x 1 , x 2 ) , 0 < y < T , x 1 R + , x 2 R , u ( 0 , x 1 , x 2 ) = φ ( x 1 , x 2 ) , u ( T , x 1 , x 2 ) = ψ ( x 1 , x 2 ) , x 1 R + , x 2 R , u ( y , 0 , x 2 ) = 0 , 0 y T , x 2 R .
        (40)
        Here, a 11 ( x 1 , x 2 ) , a 22 ( x 1 , x 2 ) , φ ( x 1 , x 2 ) , ψ ( x 1 , x 2 ) , and f ( y , x 1 , x 2 ) are given smooth functions and they satisfy every compatibility condition and
        a 11 2 ( x 1 , x 2 ) + a 22 2 ( x 1 , x 2 ) δ > 0 ,
        (41)

        and σ > 0 , which guarantees that problem (40) has a smooth solution u ( y , x 1 , x 2 ) .

        Theorem 6 For the solution of boundary value problem (40), we have the following estimate:
        u y y C ( C 2 α + β ( R + 2 ) ) + u x 1 x 1 C ( C 2 α + β ( R + 2 ) ) + u x 2 x 2 C ( C 2 α + β ( R + 2 ) ) M ( α , β ) [ φ x 1 x 1 C 2 α + β ( R + 2 ) + φ x 2 x 2 C 2 α + β ( R + 2 ) + ψ x 1 x 1 C 2 α + β ( R + 2 ) + ψ x 2 x 2 C 2 α + β ( R + 2 ) + f C ( C 2 α + β ( R + 2 ) ) ] ,

        where M ( α , β ) is independent of φ, ψ, and f.

        Proof We introduce the Banach space C ( [ 0 , T ] , E ) of all continuous abstract functions u ( y ) defined on [ 0 , T ] with values in E, equipped with the norm
        u C ( [ 0 , T ] , E ) = max 0 y T u ( y ) E .
        Note that problem (40) can be written in the form of the abstract boundary value problem
        d 2 u ( y ) d y 2 + A u ( y ) = f ( y ) , 0 < y < T , u ( 0 ) = φ , u ( T ) = ψ
        (42)

        in a Banach space E = C ( R + 2 ) with a positive operator A defined by (1). Here f ( y ) = f ( y , x 1 , x 2 ) is the given abstract function defined on [ 0 , T ] with values in E, φ = φ ( x 1 , x 2 ) , ψ = ψ ( x 1 , x 2 ) are elements of D ( A ) . Therefore, the proof of Theorem 6 is based on Theorem 5 on the structure of the fractional spaces E α ( A , C β ( R + 2 ) ) , Theorem 4 on the positivity of the operator A, on the following theorems on coercive stability of elliptic problems, nonlocal boundary value for the abstract elliptic equation and on the structure of the fractional space E α = E α ( A 1 / 2 , E ) . This is the end of the proof of Theorem 6. □

        Theorem 7 Under assumption (41) for the solution of elliptic problem
        { a 11 ( x 1 , x 2 ) 2 u ( x 1 , x 2 ) x 1 2 a 22 ( x 1 , x 2 ) 2 u ( x 1 , x 2 ) x 2 2 + σ u ( x 1 , x 2 ) = g ( x 1 , x 2 ) , x 1 R + , x 2 R , u ( 0 , x 2 ) = 0 , x 2 R ,
        the following coercive inequality holds:
        2 u x 1 2 C μ ( R + 2 ) + 2 u x 2 2 C μ ( R + 2 ) M ( μ ) g C μ ( R + 2 ) ,

        where M ( μ ) ( 0 < μ < 1 ) does not depend on g.

        The proof of Theorem 7 uses the techniques introduced in [[5], Chapter 5] and it is based on estimates (3) and (4).

        Theorem 8 ([[5], Theorem 5.2.48])

        The spaces E α ( A , E ) and E 2 α ( A 1 / 2 , E ) coincide for any 0 < α < 1 2 , and their norms are equivalent.

        Theorem 9 ([[28], Theorem 3.1])

        Let A be a positive operator in a Banach space E and f C ( [ 0 , T ] , E α ) ( 0 < α < 1 ). Then, for the solution of nonlocal boundary value problem (42), the coercive inequality
        u C ( [ 0 , T ] , E α ) + A u C ( [ 0 , T ] , E α ) M [ A φ E α + A ψ E α + M α ( 1 α ) f C ( [ 0 , T ] , E α ) ]

        holds, where M does not depend on α, φ, ψ, and f.

        Second, we consider the nonlocal boundary value problem for the elliptic equation under assumption (41)
        { 2 u ( y , x 1 , x 2 ) y 2 a 11 ( x 1 , x 2 ) 2 u ( y , x 1 , x 2 ) x 1 2 a 22 ( x 1 , x 2 ) 2 u ( y , x 1 , x 2 ) x 2 2 + σ u ( y , x 1 , x 2 ) = f ( y , x 1 , x 2 ) , 0 < y < T , x 1 R + , x 2 R , u ( 0 , x 1 , x 2 ) = u ( T , x 1 , x 2 ) , u y ( 0 , x 1 , x 2 ) = u y ( T , x 1 , x 2 ) , x 1 R + , x 2 R , u ( y , 0 , x 2 ) = 0 , 0 y T , x 2 R .
        (43)

        Here, a 11 ( x 1 , x 2 ) , a 22 ( x 1 , x 2 ) , and f ( y , x 1 , x 2 ) are given smooth functions and they satisfy every compatibility condition and (41), which guarantees that problem (43) has a smooth solution u ( y , x 1 , x 2 ) .

        Theorem 10 For the solution of initial boundary value problem (43), we have the following estimate:
        u y y C ( C 2 α + β ( R + 2 ) ) + u x 1 x 1 C ( C 2 α + β ( R + 2 ) ) + u x 2 x 2 C ( C 2 α + β ( R + 2 ) ) M ( α , β ) f C ( C 2 α + β ( R + 2 ) ) ,

        where M ( α , β ) is independent of f.

        The proof of Theorem 10 is based on Theorem 5 on the structure of the fractional spaces E α ( A , C β ( R + 2 ) ) , Theorem 4 on the positivity of the operator A, Theorem 7 on coercive stability of the elliptic problem, Theorem 8 on the structure of the fractional space E α = E α ( A 1 / 2 , E ) , and the following theorem on coercive stability of the nonlocal boundary value for the abstract elliptic equation.

        Theorem 11 ([[28], Theorem 3.1])

        Let A be a positive operator in a Banach space E and f C ( [ 0 , T ] , E α ) ( 0 < α < 1 ). Then, for the solution of nonlocal boundary value problem (40)
        { u ( y ) + A u ( y ) = f ( y ) , 0 < y < T , u ( 0 ) = u ( T ) , u ( 0 ) = u ( T )
        in a Banach space E with a positive operator A, the coercive inequality
        u C ( [ 0 , T ] , E α ) + A u C ( [ 0 , T ] , E α ) M α ( 1 α ) f C ( [ 0 , T ] , E α )

        holds, where M does not depend on α and f.

        5 Conclusion

        In the present article, the structure of the fractional spaces E α ( A , C β ( R + 2 ) ) generated by the two-dimensional elliptic differential operator A is investigated. The positivity of this operator A in a Hölder space is established. Of course, the Banach fixed point theorem and the method of the present paper enable us to establish the existence and uniqueness results which hold under some sufficient conditions on the nonlinear term for the solution of the mixed problem
        { 2 u ( y , x 1 , x 2 ) y 2 a 11 ( x 1 , x 2 ) 2 u ( y , x 1 , x 2 ) x 1 2 a 22 ( x 1 , x 2 ) 2 u ( y , x 1 , x 2 ) x 2 2 + σ u ( y , x 1 , x 2 ) = f ( y , x 1 , x 2 , u , u x 1 , u x 2 , u y ) , 0 < y < T , x 1 R + , x 2 R , u ( 0 , x 1 , x 2 ) = φ ( x 1 , x 2 ) , u ( T , x 1 , x 2 ) = ψ ( x 1 , x 2 ) , x 1 R + , x 2 R , u ( y , 0 , x 2 ) = 0 , 0 < y < T , x 2 R .

        Notes

        Declarations

        Acknowledgements

        Some of the results of the present article were announced in the conference proceeding [11] as an extended abstract without proofs. The authors would like to thank Prof. Pavel Sobolevskii (Universidade Federal do Ceará, Brasil). The second author would also like to thank The Scientific and Technological Research Council of Turkey (TUBİTAK) for the financial support.

        Authors’ Affiliations

        (1)
        Department of Mathematics, Fatih University
        (2)
        Department of Mathematics, ITTU
        (3)
        Fen Fakultesi, Matematik Bolumu, Hacettepe Universitesi

        References

        1. Fattorini HO Mathematics Studies. In Second Order Linear Differential Equations in Banach Spaces. North-Holland, Amsterdam; 1985.
        2. Grisvard P: Elliptic Problems in Nonsmooth Domains. Pitman, London; 1984.
        3. Krein SG Translations of Mathematical Monographs. In Linear Differential Equations in a Banach Space. Am. Math. Soc., Providence; 1968.
        4. Ashyralyev A, Sobolevskii PE: Well-Posedness of Parabolic Difference Equations. Birkhäuser, Basel; 1994.View Article
        5. Ashyralyev A, Sobolevskii PE: New Difference Schemes for Partial Differential Equations. Birkhäuser, Basel; 2004.MATHView Article
        6. Krasnosel’skii MA, Zabreiko PP, Pustyl’nik EI, Sobolevskii PE: Integral Operators in Spaces of Summable Functions. Noordhoff, Leiden; 1976.View Article
        7. Agarwal R, Bohner M, Shakhmurov VB: Maximal regular boundary value problems in Banach-valued weighted spaces. Bound. Value Probl. 2005, 1: 9-42.MathSciNet
        8. Alibekov KhA, Sobolevskii PE: Stability of difference schemes for parabolic equations. Dokl. Akad. Nauk SSSR 1977, 232(4):737-740.MathSciNet
        9. Alibekov, KhA: Investigations in C and L p of difference schemes of high order accuracy for approximate solutions of multidimensional parabolic boundary value problems. Dissertation. Voronezh State University, Voronezh (1978)
        10. Alibekov KhA, Sobolevskii PE: Stability and convergence of difference schemes of a high order for parabolic differential equations. Ukr. Mat. Zh. 1979, 31(6):627-634.MATHMathSciNet
        11. Ashyralyev A, Akturk S, Sozen Y: Positivity of two-dimensional elliptic differential operators in Hölder space. AIP Conf. Proc. 2012, 1470: 77-79.View Article
        12. Danelich, SI: Fractional powers of positive difference operators. Dissertation. Voronezh State University, Voronezh (1989)
        13. Lunardi A: Analytic Semigroups and Optimal Regularity in Parabolic Problems. Birkhäuser, Basel; 1995.MATHView Article
        14. Simirnitskii YuA, Sobolevskii PE: Positivity of multidimensional difference operators in the C -norm. Usp. Mat. Nauk 1981, 36(4):202-203.
        15. Sobolevskii PE: The coercive solvability of difference equations. Dokl. Akad. Nauk SSSR 1980, 201(5):1063-1066.MathSciNet
        16. Solomyak MZ:Analytic semigroups generated by elliptic operator in spaces L p . Dokl. Akad. Nauk SSSR 1959, 127(1):37-39.MATHMathSciNet
        17. Solomyak MZ:Estimation of norm of the resolvent of elliptic operator in spaces L p . Usp. Mat. Nauk 1960, 15(6):141-148.MATHMathSciNet
        18. Stewart HB: Generation of analytic semigroups by strongly elliptic operators under general boundary conditions. Trans. Am. Math. Soc. 1980, 259: 299-310. 10.1090/S0002-9947-1980-0561838-5MATHView Article
        19. Ashyralyev A: Fractional spaces generated by the positive differential and difference operators in a Banach space. In Mathematical Methods in Engineering. Edited by: Tas K, Tenreiro Machado JA, Baleanu D. Springer, Dordrecht; 2007.
        20. Hardy GH, Littlewood JE, Pólya G: Inequalities. Cambridge University Press, Cambridge; 1988.MATH
        21. Ashyralyev A, Sobolevskii PE: The linear operator interpolation theory and the stability of the difference schemes. Dokl. Akad. Nauk SSSR 1984, 275(6):1289-1291.MathSciNet
        22. Triebel H: Interpolation Theory, Function Spaces, Differential Operators. North-Holland, Amsterdam; 1978.
        23. Ashyralyev, A: Method of positive operators of investigations of the high order of accuracy difference schemes for parabolic and elliptic equations. Dissertation, Inst. of Math. of Acad. Sci. Kiev (1992)
        24. Ashyralyev A, Yaz N: On structure of fractional spaces generated by positive operators with the nonlocal boundary value conditions. In Proceedings of the Conference Differential and Difference Equations and Applications. Edited by: Agarwal RP. Hindawi Publishing Corporation, New York; 2006.
        25. Ashyralyev A, Tetikoğlu FS: The structure of fractional spaces generated by the positive operator with periodic conditions. 1470. AIP Conference Proceedings 2012, 57-60., ICAAM, 2012
        26. Bazarov MA: On the structure of fractional spaces. In Proceedings of the XXVII All-Union Scientific Student Conference ‘The Student and Scientific-Technological Progress’. Novosibirsk. Gos. Univ., Novosibirsk; 1989:3-7. (in Russian)
        27. Ashyralyev A, Nalbant N, Sozen Y: Structure of fractional spaces generated by second order difference operators. J. Franklin Inst. 2013. 10.1016/j.jfranklin.2013.07.009
        28. Ashyralyev A: On well-posedness of the nonlocal boundary value problems for elliptic equations. Numer. Funct. Anal. Optim. 2003, 24: 1-15. 10.1081/NFA-120020240MATHMathSciNetView Article

        Copyright

        © Ashyralyev et al.; licensee Springer. 2014

        This article is published under license to BioMed Central Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.